COMPETITIVE ADVANTAGE IMPROVEMENT MODEL OF PT. BANK PEMBANGUNAN DERAH JAMBI THROUGH DIGITAL LEADERSHIP AND ORGANIZATIONAL CULTURE MEDIATED BY INNOVATIVE WORK BEHAVIOR - Ayu Anggraini; Fitriaty; Lubis, Tona Aurora (Journal of Business Studies and Management Review, 2025)
This research aims toanalyzing the influence of digital leadership and organizational culture on the competitive advantage of Bank Jambi, through innovative work behavior. The research sample used was 242 respondents, taken using a simple random sampling technique. The types of data collected include primary data in the form of questionnaires on digital leadership, organizational culture, innovative work behavior, and competitive advantage, as well as secondary data in the form of other publications such as; books, journals and other documents related to the topic of this research. The data that has been collected is then analyzed using descriptive statistical analysis methods and verification analysis in the form of Partial Least Square (PLS). The results of the direct effect analysis prove that; (1) digital leadership and organizational culture directly have a significant effect on innovative work behavior, (2) digital leadership, organizational culture, and innovative work behavior directly have a significant effect on competitive advantage, (3) digital leadership indirectly has a significant effect on competitive advantage, through innovative work behavior, and (4) organizational culture indirectly has a significant effect on competitive advantage, through innovative work behavior. The results of this study have implications for efforts to improve innovative work behavior and competitive advantage of Bank Jambi, through a more adaptive corporate culture, as well as improving the quality of digital leadership, especially in terms of change management competency